Children's Understanding of Thermal Phenomena in Initial Science Instruction - Sanja Ž. Balać; Маrija T. Bošnjak Stepanović; Ivana Z. Bogdanović (University of Belgrade, Teacher Education Faculty, 2022)
The method of interpreting thermal phenomena in the lower grades of primary school, which avoids explaining these phenomena based on the particle structure of a substance, gives room for pupils' alternative ideas. The aim of this paper is to determine the level of pupils' understanding of thermal phenomena in the lower grades of primary school. For this purpose we developed a test of knowledge of the following concepts: aggregate states of a substance, substance structure, temperature, heat, and heat conduction. The research was carried out in primary schools in the towns of Sombor and Kikinda and the sample consisted of 475 pupils. According to the obtained results, the lowest achievement, between 0% and 20% of the maximum points, is observed much more among the pupils of the first and second grades of primary school than among the pupils of the higher grades. In all grades the majority of the pupils had between 20% and 40% of the maximum number of points. There were no pupils with the highest scores. There was no significant statistical difference in terms of achievement bewtween the first and second grade pupils, nor between the third and fourth grade pupils, whereas this difference is statistically significant in other, higher pairs of grades (the final two grades had the highest level of achievement). The research confirmed that there is an insufficient impact of instruction on the level of understanding thermal phenomena among the pupils of the lower grades, which requires finding new approaches to teaching this type of content.